Evaluation and metrological performance of a novel ionisation vacuum gauge suitable as reference standard - Jousten, Karl (2023)
Funding Information: This work has received funding from the EMPIR programme (projects 16NRM05 and 20SIP01) co-financed by the Participating States and from the European Union's Horizon 2020 research and innovation programme and the Portuguese National Funding Agency for Science, Research and Technology in the framework of the project UIDB/FIS/ 00068/2020. Publisher Copyright: © 2023 The Author(s)